In Vivo Antidiabetic Activity of Aqueous Extract of Psidium Quajava in Alloxanised Diabetic Mice - IK, Njangiru (Journal of Medical Biomedical and Applied Sciences, 2017)
Psidium quajava has for long been employed in the management of many diseases in Kenya, including diabetes mellitus. However, the use of this plant extract lacks scientific validation in regard to its efficacy. This study aimed at investigating in vivo antidiabetic activity of aqueous extract of Psidium quajava in alloxanized diabetic mice. Antidiabetic property was assessed through oral and intraperitoneal administration of aqueous plants extract at doses of 50, 100, 200 and 300mg/kg body weight and profiling the levels of blood glucose after 0, 1, 2, 3, 4, 6 and 24 hours using a glucometer. The mineral composition of the aqueous plant extract was assayed using Total Reflection X-ray Fluorescence system (TRXF), while the different types of secondary metabolites were assessed using standard procedures. The aqueous plant extract exhibited a dose dependent hypoglycemic activity in alloxanized diabetic mice. The studied plant extract contained alkaloids, flavonoids, saponins, tannins, and total phenols at varying concentration. The mineral profile demonstrated the presence of detectable levels of K, Ca, Ti, V, Mn, Fe, Ni, Cu, Zn and As. The plantâs aqueous extract was effective in lowering blood glucose levels.